The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/jeim-07-2018-0169
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain network and information sharing effects of SMEs’ credit quality on firm performance

Abstract: Purpose The purpose of this paper is to examine how a supply chain (SC) network helps small and medium enterprises (SMEs) to obtain liquidity and working capital for enhancing their performance while developing the relationships among SC members through information sharing. Moreover, this study also investigates whether a strong tie or bridge tie improves the availability of SMEs’ credit and performance. Design/methodology/approach Using a survey approach, data were collected from textile SMEs, located in Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 78 publications
7
83
0
1
Order By: Relevance
“…A sample size of 15 literature studies was viewed to be adequate in terms of providing the data for the statistical analysis. As noted by previous researchers (Mashenene and Rumanyika, 2014;Mohammed et al, 2013;Ali et al, 2019), a sample size of no less than 12 items of literature is sufficient to extract the variables for analysis.…”
Section: Titlementioning
confidence: 99%
See 1 more Smart Citation
“…A sample size of 15 literature studies was viewed to be adequate in terms of providing the data for the statistical analysis. As noted by previous researchers (Mashenene and Rumanyika, 2014;Mohammed et al, 2013;Ali et al, 2019), a sample size of no less than 12 items of literature is sufficient to extract the variables for analysis.…”
Section: Titlementioning
confidence: 99%
“…Eckstein et al (2014) suggests that SCM helps firms to adopt agility, which in return positively affects both costs as well as operational performance. Ali et al (2019) found that SCM positively and significantly helps SMEs to obtain liquidity, working capital and to improve member relationships. Notwithstanding the benefits of SCM in organisations, various studies have documented the impediments that stand in the way of successful SCM implementation.…”
Section: Supply Chain Management (Scm)mentioning
confidence: 99%
“…Although previous research on SCF has discussed how network structural characteristics affect CFP, (e.g. Carnovale et al (2019) consider EC and network density, and Ali et al (2019) consider strong ties and bridge ties in supply chain networks), our research is the first to expand the analysis into FSCs, an important branch of SCF. Moreover, compared with previous SCF studies based on the network organisation, such as Seiler et al (2020), our research offers a broader view of the SCF network organisation by detailed evidencing that network structural characteristics affect CFP based on both network centrality (EC, CL, and BC) and network power (ND, NS, and CC).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…[53] integrates supply and demand across companies." [59] discovered that SCM undoubtedly and significantly promotes SMEs to achieve liquidity, working capital and to improve member connections. Notwithstanding the advantages of SCM in institutions, numerous investigations have documented the difficulties that attain in the way of successful SCM implementation.…”
Section: Two Level Supply Chain In Smesmentioning
confidence: 99%